The role of social networks in reducing educational loss among primary level students from the point of view of Al Sera basic school teachers in the South Hebron Directorate of Education (Qualitative study) - Rjoub, Sahar; Arman, Ibrahim (Journal of Curriculum and Teaching Methodology, 2024)
This ongoing study aimed to detect teachers’ perceptions about the role of social networks in reducing educational loss among primary level students. To achieve this goal, the study used qualitative research based on the case study approach. The number of participants in the study was (8) primary level teachers. Using a semi-structured interview tool, the thematic analysis method was used to analyze the data. The results of the study resulted in deducing four topics directly related to the role of social networks in reducing educational loss. The topics were as follows: Social networking tools used in teaching, organizing student interaction using social networks, educational strategies used via social networks, using social networks to evaluate student performance. Based on the results, the study recommended employing social networks to build programs and mechanisms to support the educational process with clear steps to reduce educational loss among students, and changing the traditional teaching style by introducing various technologies such as video and scientific presentations, and employing educational networks in teaching inside or outside the classroom, Conducting a scientific evaluation of students’ participation via social networks that takes into account the standards of good evaluation, such that it uses standards for diagnosis, construction, treatment, and continuous follow-up, and conducting further studies to determine the importance of social networks in the educational process, and conducting future studies that will be more in-depth in understanding the various challenges facing teachers while employing networks. Social networking in teaching, and establishing training programs aimed at developing teachers’ skills in using social networks in the educational process.